Environmental management systems handbook for refineries - Saini, Nitin (SCITUS Academics LLC, 2016)
Refinery operations in complying with environmental laws and improving the overall efficiency of their operations. The author's approach has been recognized internationally as an integrated model that captures improved compliance and financial savings by reducing operating costs through dedicated pollution prevention programs. The focus is on refinery operations; however, the principles and general discussions are applicable to all manufacturing sectors. All business operations are faced with global challenges involving dynamic interactions between changing regulations, market competitiveness, and spiralling costs for raw materials and labour. It is impossible to separate environmental management issues and infra-structure investments from the primary strategies of any business. In fact, any company, facility, or refinery that focuses on pollution control as opposed to environmental management will not find itself in business over the next decade. There simply are too many costs and financial exposures to businesses that do not focus on continual improvement of their environmental performance. A commitment to continual improvement of environmental performance is increasingly becoming the standard of care for industry.